Trends of activity daily life (ADL) and mental health problems among middle-aged and elderly in Indonesia using IFLS 4 and IFLS 5 - Lestari, Nur Cahyani Ari; Barkinah, Tut; Utami, Syahrida Wahyu; Wahyuni, Rahmawati; Deananda, Deananda; Putri, Rosalin Ariefah (Science Midwifery, 2024)
Indonesia is facing an aging society since the proportion of the elderly was almost 10% of the total population. This situation is reflected by the increasing total number of elderlies, dependency ratio, and life expectancy. Aim: This study aimed to describe the distribution of total score of mental health and activity daily life (ADL) among middle age and elderly in Indonesia. This study used pooled data from Indonesia Family Life Survey (IFLS) wave 4 and wave 5. It was conducted in 2007 and 2014. The sample size of this study consisted of middle age (40 to 59 years old) and elderly (60 years old and up). Results: The findings of this study revealed that from 2007 to 2014, the total score of mental health problems was increasing, and also the total score of activity daily life (ADL). Middle age and elderly in Indonesia had an increased number of depressions, but the total majority of them had a higher ability to do daily activity life (ADL). According to an aging population that faced the Indonesian population, this study can describe the increasing number of depressed but increasing their ability of them to do daily activity life (ADL).